Dune : House Corrino / 3. - Herbert, Brian (Bantam Spectra book, 2002)
Duke Leto Atreides, is an royal underdog desperate to free the Ixians from their oppressors and the plot of the Imperial House Corrino that threatens to end space travel by producing a synthetic form of melange.